PERBANDINGAN BEBAN KERJA LAMA WAKTU PELAYANAN MAHASISWA PPDS 1 DAN DPJP DALAM PELAYANAN PASIEN DI RUMAH SAKIT - Guntur Surya Alam; Laksono Trisnantoro; Darwinto (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: RSUP dr Sardjito, as the primary teaching hospital of FK UGM received many PPDS1. PPDS 1 makes a significant contributionto patient care. PPDS1 at work has not been considered a hospital worker. Meanwhile, PPDS1 has the right as a temporaryofficial hospital worker while taking specialization education.Objective: This study aims to determine differences in the workload.Methods: This is observational research with direct observation of the length of time for DPJP and PPDS1 service activities accordingto the type of activity. The research subjects were PPDS1 from KSM General, KSM Pediatric Surgery, KSM Urology, KSM Pediatrics atvarious levels. Data analysis was carried out by compiling and calculating the group average of invasive and non-invasive medicalprocedures and the average of all.Results: The extended workload of PPDS1 and DPJP student services in pediatric surgery services carried out by red pin residentsis approximately 35%, yellow pin residents and 25%, green pin residents 25, and DPJP about 15%. In general surgery services,about 28% red residents, 24% yellow pin residents, 25% green pin residents, and 23% DPJP. In urology services, about 28% red pin residents, 25% yellow pin residents, 28% green pin residents, and 19% DPJP. UPA residents with red pins are 8%, yellow pin residentsare 23%, green pin residents are 59%, and DPJP is 10%. During the pandemic, the proportion of service time, in general, was 82% held by residents.Conclusion: The workload for red pin residents is 24%, yellow pin residents 24%, green pin residents 34%, and DPJP 18%. Duringthe pandemic, the proportion of surgical service time, in general, was carried out by residents. Service responsibility remains with DPJP even though the length of direct service to patients is only 18% on average.